Critical path (New York St. Martin's Press, 1981)
Includes chronologies of scientific discoveries and world events.
Includes index.
Keywords: Civilization, Modern -- 1950-; Civilization; Civilisation -- Histoire; Civilisation -- 1950-; Sociale verandering; Technologie